PEMBELAJARAN BAHASA INGGRIS BERBASIS MULTIMEDIA (Studi Kasus : PAUD AL-HASANAH CILIMBUNG TASIKMALAYA) - Yahdi Kusnadi; . Sismadi; . Nasruloh (Universitas Bina Sarana Informatika, 2018)
Mastering the English language is a skill that is very important in the era of information and communication today as capital for extensive social and career support, aware of the importance of mastering the language it needs to be taught from an early age education of course, need guidance and referrals from teachers and parents, this time in PAUD Al-Hasanah Cilimbung Tasikmalaya learning still use the traditional that is by writing and drawing materials on the blackboard and still incomplete supporting facilities for learning materials of course this is less effective and efficientstudents feel less understanding and less an interest on the material being taught, to overcome these problems then needed a new way of learning the English language is by using interactive media technology which expected to be able support the optimization learning fun so as to improve the English language skills that are taught accordance In designing animated multimedia-based English language learning done using Adobe Flash CS5 and Adobe Photoshop CS6. After designing and implementing multimedia models in multimedia-based English language learning on PAUD Al-Hasanah Cilimbung Tasikmalaya then the result turns out that students and teachers are very happy.Keyword: Learning English, multimedia, adobe flash CS5, adobe photoshop CS6